Khayyam and Russian Poets (Reviewing Khayyam’s Position and Research on Khayyam in Russia) - Marzieh Yahyapour; Janolah Karimi-Motahhar; Tatiana Vladimirovna Maltsea (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Khayyam, a poet from the "saffron shores" with worldwide fame, is on the top of Russian poetry and literature because of his charming, thoughtful, and philosophical quatrains, along with other poets of the "ancient land" of Iran. The present article aims at introducing and criticizing the translations of Khayyam’s quatrains into Russian and showing the influence of his poems and ideas on Russian translators and poets. Russian translators, Iranologists, diplomats, and poets played a significant role in introducing Khayyam to the Russian society. Book of poems of Toreverov, Chachikov, Surkov, Kedrin, Ivanov, Sannikov, Vinokurov, Plisetsky, Yesenin, and Gamzatov devoted some pages to Khayyam. Studies indicate that in addition to praising Khayyam, Russian poets sometimes began to express the idea of their work with a word from Khayyam as the epigraph of their poems. Studies indicate that for most thinkers, Khayyam’s quatrains are the source of inspiration for philosophical and mystical ideas and a source for saturating the spiritual void, understanding the "mysteries of eternity", solving the riddle of the "ancient world" and cosmology. Investigating the poems studied in the article indicate that Khayyam’s quatrains opened the mysterious doors of the universe to most Russian thinkers and readers and let them taste the wine of the universe, although some of them had different interpretations of Khayyam’s poems due to contradictions in his poems.